An onco-geriatric approach to select older patients for optimal treatments of pancreatic adenocarcinoma. Issue 4 (July 2018) - Castel-Kremer, Elisabeth; De Talhouet, Solene; Charlois, Anne-Laure; Graillot, Emmanuelle; Chopin-Laly, Xavier; Adham, Mustapha; Comte, Brigitte; Lombard-Bohas, Catherine; Walter, Thomas; Boschetti, Gilles
Abstract: Introduction: Pancreatic adenocarcinoma affects mainly older patients. Surgery is indicated for localized tumors while chemotherapy alone is proposed in advanced or metastatic tumors. Objective: To evaluate the feasibility of standard of care oncologic treatments in this population, the accuracy of the geriatric evaluation to predict the ability of patients to tolerate the recommended treatments and to identify specific geriatric prognosis factors. Methods: We included, between 2007 and 2014, all consecutive patients over 70 years of age with a pathologically diagnosed pancreatic cancer. The patients underwent a comprehensive geriatric assessment before therapeutic decision in a multidisciplinary team meeting. We analyzed factors independently associated with all-cause mortality with Cox survival analysis. Results: Seventy-three patients (median age = 77.9 years) were prospectively included. Among them, 42 patients underwent surgery whereas the 31 other patients not eligible for surgical treatment received chemotherapy ( n = 22) or best supportive care alone ( n = 9). Almost 62% of operated patients received adjuvant chemotherapy. In the non-surgical group, a mean of 9 cycles of palliative chemotherapy per patients were administrated. Median overall survival was 21.3 months in the surgical group and 6.1 months in the palliative group ( p = 0.0001). Most of oncologic parameters were found to be independent survival predictors. Age was not associated with the survival, but a significant impact of Lawton ' s Instrumental Activities of Daily Living (IADL) impairment (IADL<4) (HR = 5.0, p = 0.047), Cumulative Index Rating Scale-Geriatric (CIRS-G) ≥2 (HR = 19, p = 0.035) and weight loss >10% (HR = 4.6, p = 0.03) on survival was detected. Surgery was the only factor independently predictive of survival in multivariate analysis ( p < 0.001). Conclusion: Almost 90% of selected older pancreatic patients with cancer (64 out of 73 patients) may benefit from the same standard treatments as younger patients. IADL impairment of patients, CIRS-G ≥2, and weight loss >10% constitute survival prognostic factors which should be added to the oncological criteria in the therapeutic decision-making process.